Hypoxic dose, intensity distribution, and fatigue monitoring are paramount for "live high-train low" effectiveness - Brocherie, F.; Schmitt, L.; Millet, G. P. (European Journal of Applied Physiology, 2017)
Letter to the editor: Bejder, J., Andersen, A. B., Buchardt, R., Larsson, T. H., Olsen, N. V., & Nordsborg, N. B. (2017). Endurance, aerobic high-intensity, and repeated sprint cycling performance is unaffected by normobaric "Live High-Train Low": a double-blind placebo-controlled cross-over study. European journal of applied physiology, 117(5), 979-988.